2014
DOI: 10.1016/j.bpj.2013.11.3216
|View full text |Cite
|
Sign up to set email alerts
|

S. Aureus Adapt to Growth Conditions by Changing Membrane Order

Abstract: a finite number of agents utilizing a velocity alignment interaction and a Lennard-Jones potential, which provides both cohesive and repulsive interactions between neighboring agents. In the swarming regime of our model, an agent is selected at random to ''escape'' the flock, by choosing a particular direction to travel in, and no longer align with it's neighbors. We found that close to the swarming transition the escapee was unable to escape, while deeper in the swarming regime the swarm was more stable and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Calorimetric experiments were performed to determine the effect of carotenoids on the S. aureus membranes. Phosphatidylglycerol (PG) is the most abundant lipid (80%) in the outer monolayer and CL is a minor component (20%) [ 5 , 23 , 24 ]. Thermograms of the MLV made of DMPG, CL, and DMPG:CL (80:20) are summarized in Figure 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…Calorimetric experiments were performed to determine the effect of carotenoids on the S. aureus membranes. Phosphatidylglycerol (PG) is the most abundant lipid (80%) in the outer monolayer and CL is a minor component (20%) [ 5 , 23 , 24 ]. Thermograms of the MLV made of DMPG, CL, and DMPG:CL (80:20) are summarized in Figure 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the effect of LyeTx I mn∆K on MRSA membranes, we studied the peptide–membrane interaction in the presence of POPG:CL (2:1, mol/mol). This phospholipid composition was selected as it represents the predominant constituents of S. aureus membranes [ 43 , 44 , 45 ]. Initially, the thermodynamic studies regarding the membrane interactions of LyeTx ImnDK with POPG:CL LUVs indicated that the peptide presents a moderate to high affinity with negatively charged vesicles at 35 °C.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the effect of LyeTx I mn∆K on MRSA membranes, we studied the peptide-membrane interaction in the presence of POPG:CL (2:1, mol/mol). This phospholipid composition was selected as it represents the predominant constituents of S. aureus membranes [43][44][45]. Initially, the thermodynamic studies regarding the membrane interactions of LyeTx ImnDK with POPG:CL LUVs indicated that the peptide presents a moderate to high affinity with negatively charged vesicles at 35 • C. Although, the negative enthalpy values indicate exothermic binding of the peptides to the anionic vesicles and the predominance of attractive Coulomb forces, the binding process for the peptide is mainly driven by entropic factors, since |T∆S| >> |∆H|.…”
Section: Discussionmentioning
confidence: 99%